Strengthening the Civil Aspect of Environmental Law as an Instrument of Sustainable Development - Utami, Mieke Aprilia (Pusdikra-Publishing.com, 2025)
Over the past ten years, the environmental law discourse has undergone a paradigmatic shift from a dominant approach of administrative and criminal nature to a stronger integration with civil principles. This transformation is driven by the increasing need for legal mechanisms that are not only repressive, but also restorative and preventive in accommodating the sustainable development agenda. This research aims to analyze the urgency and strategies for strengthening the civil aspect in the Indonesian environmental law system as an effective instrument in promoting ecological responsibility and intergenerational justice. Using normative juridical approaches and analysis of various court decisions, laws and regulations, and international instruments related to the environment, this study finds that civil aspects particularly civil liability, environmental compensation, and class action lawsuits have great potential in encouraging corporate accountability and expanding community participation. The growing practice of environmental litigation, both through citizen lawsuits and the principle of polluter pays, shows a tendency to strengthen the role of civil law in fighting for the right to a clean and healthy environment, as mandated in Article 28H of the 1945 Constitution. However, the effectiveness of the civil approach is still hampered by the limitations of judicial infrastructure, the uncertainty of ecological compensation norms, and the suboptimal role of judges in adopting international environmental law principles such as the precautionary principle and sustainable responsibility. Therefore, policy reformulation and institutional capacity building are absolute prerequisites in making civil law a strategic pillar in sustainable development.